Polymorphism of renin — angiotensin system genes in progression of liver fibrosis in patients with chronic hepatitis C - O. V. Taratina; T. N. Krasnova; L. M. Samokhodskaya; T. N. Lopatkina; V. A. Tkachuk; N. A. Mukhin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
Aim of investigation. To estimate relation of polymorphism of genes encoding reninangiotensin system components (AGT G-6A, AGT M235T and ATR1 A1166C) with rate of liver fibrosis progression in patients with chronic hepatitis C (CHC).Material and methods. Overall 109 patients with CHC and liver cirrhosis C with established stage of fibrosis and duration of disease have been divided into group of «rapidly progressing fibrosis» (55 patients, ≥0,130 fibrosis points/year) and «slowly progressing fibrosis» (54 persons, <0,130 fibrosis units/year). Assessment of polymorphism of studied genes was carried out by molecular genetic methods.Results. In CHC patients of «rapidly progressing fibrosis» group in comparison to «slowly progressing fibrosis» group minor A-allele (50,0 and 33,3% respectively, p=0,0126) and «mutant» АА-genotype (27,3 and 11,1%, р=0,0324; OR АА=3,00; 95% CI 1,07-8,45), AGT gene on locus G-6A, as well as minor T-allele (р=0,0407) of AGT gene in M235T locus were significantly more common while MM genotype of M235T polymorphism of AGT gene (20,8 and 44,4%, respectively, p=0,0090; OR MM=0,33; 95%-CI 0,15–0,73) were significant less frequent. No significant differences between groups in distribution of alternative alleles and genotypes of ATR1 gene on A1166C locus have been revealed.Conclusion. Carriage of mutant alleles of angiotensinogen gene on any of loci (G-6A or M235T) is the factor predicting more rapid progression of disease. As chronic hepatitis C is multifactorial disease, it is rational to use testing of allelic variants of angiotensinogen gene in patient-specific approach at CHC management.